Seasonal habitat drives intestinal microbiome composition in anadromous Arctic char (Salvelinus alpinus). (4th June 2020) - Element, Geraint; Engel, Katja; Neufeld, Josh D.; Casselman, John M.; van Coeverden de Groot, Peter; Greer, Charles W.; Walker, Virginia K.
Summary: Intestinal microbial communities from 362 anadromous Arctic char ( Salvelinus alpinus ) from the high Arctic Kitikmeot region, Nunavut, Canada, were characterized using high‐throughput 16S rRNA gene sequencing. The resulting bacterial communities were compared across four seasonal habitats that correspond to different stages of annual migration. Arctic char intestinal communities differed by sampling site, salinity and stages of freshwater residence. Although microbiota from fish sampled in brackish water were broadly consistent with taxa seen in other anadromous salmonids, they were enriched with putative psychrophiles, including the nonluminous gut symbiont Photobacterium iliopiscarium that was detected in >90% of intestinal samples from these waters. Microbiota from freshwater‐associated fish were less consistent with results reported for other salmonids, and highly variable, possibly reflecting winter fasting behaviour of these char. We identified microbiota links to age for those fish sampled during the autumn upriver migration, but little impact of the intestinal content and water microbiota on the intestinal community. The strongest driver of intestinal community composition was seasonal habitat, and this finding combined with identification of psychrophiles suggested that water temperature and migratory behaviour are key to understanding the relationship between Arctic char and their symbionts.